Communities of Phragmites australis (Cav.) Trin.ex Steud. in the fluvial terrace of Lower Danube: their diversity and structure of the above-ground phytomass - Valchev, V. (Biologica Nyssana, 2017)
Determination of stocks of aboveground phytomass of reed communities in Bulgaria is not well studied yet. This survey is the most detailed study on the stocks of the aboveground phytomass of the reed communities (Phragmites australis (Cav.) Trin. Ex Steud.) in Bulgaria. The studied reed beds are formed in the floodplain part of the Danube River. They are located in the fluvial terrace of the river between Archar Village (west) and Srebarna Village (east). As a result of the survey, it was found that the average stocks of the aboveground phytomass of the reed communities reached to 19.78 t/ha. Moreover, 54.04% of the aboveground phytomass is concentrated in the stems of the reed plants. Almost 42% of it is produced by the leaves, and the inflorescences produce less than 5% of the total amount of the phytomass. This study once again demonstrates the important role of reed beds for the normal functioning and development of riparian ecosystems.